The Influence of Social Support, Work-Life Balance, and Job Burnout on Project Performance: The Moderating Role of Organizational Support on Health Workers at Cilacap Regional General Hospital - Ramdhani Larasati, Lintang; Justiana Astuti, Herni; Hariyanto, Eko; Rachmawati, Erny (Universitas Muhammadiyah Pontianak, 2026)
This study aims to examine the effect of social support, work-life balance, and job burnout on project performance, with organizational support as a moderating variable. The study involved 120 healthcare workers at Cilacap Regional General Hospital using a quantitative approach and SEM-PLS analysis. The findings reveal that social support and job burnout significantly influence project performance, while work-life balance does not. Additionally, organizational support does not moderate the relationships among those variables. These results emphasize the importance of managing burnout and enhancing interpersonal support in improving project effectiveness in the healthcare sector under high workload pressure.